Securing SQL server protecting your database from attackers - Cherry, Denny (Elsevier Syngress, 2015)
In Securing SQL Server, Third Edition, you will learn about the potential attack vectors that can be used to break into SQL server databases as well as how to protect databases from these attacks. In this book, Denny Cherry - a Microsoft SQL MVP and one of the biggest names in SQL server - will teach you how to properly secure an SQL server database from internal and external threats using best practices as well as specific tricks that the author employs in his role as a consultant for some of the largest SQL server deployments in the world